Suicide and suicide attempts by the elderly in film: related factors as shown in feature films - Scalco,Laércio Maciel (2016)
Abstract Objective: to analyze cases of suicide and suicide attempts by elderly persons in feature films. Method: a survey of specialized internet cinema portals was carried out. A total of 19 feature films produced between 1950 and 2014 were identified. After the authors watched the films, synopses were written describing the circumstances of the suicide and dialogue that described the profile of the elderly character was transcribed. Results: films that described suicide among the elderly were classified as follows: male gender in 13 films (68%), depression with hopelessness in 12 (63%), existence and efficiency of health services, physical illness and absence of familiar support in ten (for each category) (53%), cognitive rigidity in eight (42%), suicidal thinking in seven (37%), dysfunctional assumptions and a self-perception of negativity in six (32%), problem-solving deficits in five (26%) and a lack of social support in five (26%). Conclusion: the portrayal of suicide among the elderly in films helps to raise awareness of this subject and prevent it.